Calibrating a hec-ras model of broad crested weir as inline structure using open channel flume flow method and its application for sediment transport - Ong, Ming Zhang (2014)
HEC-RAS have been used for almost 20 years and up till today HEC-RAS has difficulty in the stimulation of a steep channel or stream. Besides that, many users around the world find instability numerical unsteady flow when using HEC-RAS. Confusion may arise among the engineers whether this software is reliable and appropriate on certain condition. The objective of this study is to compare the results of the water surface profile between HEC-RAS and the experiments in the laboratory. The other main objective of this study is to obtain the appropriate manning value of the open channel in the laboratory. The procedure and the method to collect data with consideration of reliability and feasibility will also be described. The research can be divided into four phases, which are laboratory work, manning value specification, computational work, and analyze results. HEC-RAS software will determine the upstream and downstream water surface profile with different range of discharge and manning value. Once the HEC-RAS and lab experimental result is obtained, comparison is made. Calibration between laboratory experimental result and HEC-RAS's result is to determine whether this software is reliable to be used on certain condition. Prediction of the sediment transport pattern in the upstream and the downstream part of broad crested weir is determined. The duration of HEC-RAS and lab experimental required 2 semesters. From the result and discussion, the appropriate Manning value is 0.009 s/rn"3 with the root mean square error of 0.0165 in at the distance of 2 m from upstream and the sediment transport occurs at the upstream. This research has shows that the HECRAS is still reliable software on these conditions.